2015
DOI: 10.1002/chem.201503044
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective [3+2] Carbocyclization of Indole‐Derived Imines and Electron‐Rich Alkenes: A Divergent Synthesis of Cyclopenta[b]indole or Tetrahydroquinoline Derivatives

Abstract: An unprecedented stereoselective [3+2] carbocyclization reaction of indole-2-carboxaldehydes, anilines, and electron-rich alkenes to obtain cyclopenta[b]indoles is disclosed. This pathway is different from the well-established Povarov reaction: the formal [4+2] cycloaddition involving the same components, which affords tetrahydroquinolines. Moreover, by simply changing the Brønsted acid catalyst, this multicomponent coupling process could be divergently directed towards the conventional Povarov pathway to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It was found that the model coupling reaction could be changed to give related products 139 or 140 in the presence of different acid catalysts ( Schemes 60 and 61 ). 126 …”
Section: Multicomponent Reactions Of Indolesmentioning
confidence: 99%
“…It was found that the model coupling reaction could be changed to give related products 139 or 140 in the presence of different acid catalysts ( Schemes 60 and 61 ). 126 …”
Section: Multicomponent Reactions Of Indolesmentioning
confidence: 99%
“…In 2015, Alicia Galván and co-workers proposed a Bronsted or Lewis acid-catalyzed multicomponent coupling reaction involving indole-2-carboxaldehydes 28, anilines 92 and electron-rich alkenes 93a via a stereoselective [3 + 2] cyclization pathway to obtain cyclopenta[b]indole derivatives 94 (Scheme 13). [65] This new pathway (colloquially referred to as anti-Povarov reaction) was different from the conventional Povarov reaction involving [4 + 2] In 2016, Galván and co-workers reported a multicomponent coupling reaction for the enantioselective synthesis of pyrrolo [1,2-a]indoles from indole-2-carboxaldehydes, amines and enolethers through an acid-catalyzed [3 + 2] cyclization process (Scheme 14). [66] The experiments were carried out with 1Hindole-2-carboxaldehyde 1 and 2,3-dihydrofuran 93b as model substrates.…”
Section: Synthetic Methodologies and Total Synthesismentioning
confidence: 99%
“…Bronsted acid-catalyzed multicomponent coupling reaction involving indole-2-carboxaldehydes, anilines and electron-rich alkenes. [65] molecular hydroacylations of the N-allylindole-2-carboxaldehydes containing phenyl (104g), 4-methoxyphenyl (104h), and 4-chlorophenyl (104i) substituents at the terminal carbon of the allyl unit afforded the corresponding products in good yields (80-99 %). The five-and six-membered nitrogen-containing heterocyclic ketones obtained from hydroacylation reac-Scheme 14.…”
Section: Synthetic Methodologies and Total Synthesismentioning
confidence: 99%
“…These contributions lead to a significant demand for effective methods and tactics for constructing these architectures and their derivatives. Strategies for cyclopenta­[ b ]­indole syntheses are mainly divided into several annulation approaches with different reaction systems, which often include traditional Fischer indole synthesis, intramolecular Friedel–Crafts cyclization and Nazarov cyclization reaction, and other methods . Despite these successful examples, some critical issues, particularly concerning substrate scope and regioselectivity, remain unsolved and are full of challenge.…”
mentioning
confidence: 99%